SIGNIFINCANCE AND APPLICATION OF PSYCHOLINGUISTICS ON ENGLISH TEACHING USING LMS - Ariati, Jumerli; Elsara, Wenny (Jurnal Ilmiah Spectral, 2025)
This study investigates the pedagogical implications of integrating psycholinguistic principles into English language instruction through the strategic use of Learning Management Systems (LMS), specifically Google Drive, Google Classroom,and Zoom. Employing a qualitative case study approach, the research was conducted with seven students enrolled in a psycholinguistics course within the English Literature program at Persada Bunda Indonesia University. Data collection involved triangulated methods, including classroom observations, reflective journals, semi-structured interviews, and document analysis of student outputs. The findings reveal that embedding psycholinguistic concepts within LMS-based instruction significantly enhanced learners’ understanding of language processing mechanisms in the brain. Moreover, it fostered thedevelopment of metacognitive strategies and promoted learner autonomy in English language acquisition. Each LMS tool played a distinctive role in supporting psycholinguistic dimensions of learning: Zoom facilitated real-time language productionand interaction; Google Classroom provided a platform for structured linguistic input and cognitive engagement; while Google Drive promoted collaborative construction of meaning and reflective learning practices. The study concludes that the integration ofpsycholinguistic theory with digital learning environments can enrich the quality of English language education. Such an approach aligns instructional practices with cognitive processes, thereby fostering more effective, engaging, and learner-centered pedagogy in higher education settings.